2021
DOI: 10.1136/neurintsurg-2020-017243
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the pathogenesis of cerebral fusiform aneurysms: high-resolution MRI and computational analysis

Abstract: BackgroundIntracranial fusiform aneurysms are complex and poorly characterized vascular lesions. High-resolution magnetic resonance imaging (HR-MRI) and computational morphological analysis may be used to characterize cerebral fusiform aneurysms.ObjectiveTo use advanced imaging and computational analysis to understand the unique pathophysiology, and determine possible underlying mechanisms of instability of cerebral fusiform aneurysms.MethodsPatients with unruptured intracranial aneurysms prospectively underwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 34 publications
1
27
0
Order By: Relevance
“…Although the exact nature of such enhancement will remain a matter of some conjecture, based on its consistency we propose that it reflects both the unprecedented spatial resolution and remarkable sensitivity of MRI to small concentrations of modern high-relaxivity gadolinium chelates, the latter exceeding the sensitivity of X-ray based techniques to iodine by several orders of magnitude 18 19. Notably, five aneurysms in our series were morphologically fusiform, previously reported to enhance more strongly, which may partly explain the results 20…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Although the exact nature of such enhancement will remain a matter of some conjecture, based on its consistency we propose that it reflects both the unprecedented spatial resolution and remarkable sensitivity of MRI to small concentrations of modern high-relaxivity gadolinium chelates, the latter exceeding the sensitivity of X-ray based techniques to iodine by several orders of magnitude 18 19. Notably, five aneurysms in our series were morphologically fusiform, previously reported to enhance more strongly, which may partly explain the results 20…”
Section: Discussionsupporting
confidence: 73%
“…Accordingly, previously reported approaches to normalization and internal signal references may be beneficial additions to the subjective, qualitative approach described herein 31 32. Moreover, the enhancement might be related to other phenomena, including thickening of the arterial wall, associated vasculopathy, thrombosed aneurysms, or artifactual sources 20 33 34…”
Section: Discussionmentioning
confidence: 88%
“…An average of 62 spokes per mm 2 were generated. Only saccular aneurysms were included in the morphological analysis (Table 1 ) as it has been described that fusiform aneurysms undergo different biological processes 19 . The entire cohort was included in validation of the AWE semi-automated method.…”
Section: Resultsmentioning
confidence: 99%
“…However, other studies reported a higher risk of hemorrhage for FIAs larger than 10 mm ( 22 , 23 ). Furthermore, a very recent MRI study by Sabotin et al ( 24 ) demonstrated the presence of increased contrast enhancement in FIAs, which was associated with microhemorrhage and pathophysiological processes.…”
Section: Discussionmentioning
confidence: 97%